1993
DOI: 10.1021/ja00054a033
|View full text |Cite
|
Sign up to set email alerts
|

The role of the sugar and chlorine substituents in the dimerization of vancomycin antibiotics

Abstract: Copyright 2007 Elsevier B.V., All rights reserved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
1
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 2 publications
1
142
1
3
Order By: Relevance
“…The affinity constant for Aglu towards KAA was three times less than that of V, in agreement with data cited previously in the literature. [6,37] Aglu was found to have a higher affinity for LII than for KAA, nevertheless, it is still nearly 10 times lower than that of V.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The affinity constant for Aglu towards KAA was three times less than that of V, in agreement with data cited previously in the literature. [6,37] Aglu was found to have a higher affinity for LII than for KAA, nevertheless, it is still nearly 10 times lower than that of V.…”
Section: Resultsmentioning
confidence: 86%
“…For example, the sugar residues may positively influence glycopeptide binding to the bacterial cell wall, as well as possibly interfering with the trans-glycosylation process during the formation of the peptidoglycan. [6,38] Another factor that contributes to antibiotic efficacy is the possibility of noncovalent dimerization of some glycopeptide antibiotics. [39] It has been reported in the literature that cooperativity may induce glycopeptide antibiotics to dimerize upon binding to bacterial cell-wall analogues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the disaccharide group shown in Figure 3 is not essential for the ligand recognition [33], derivatization of the dye on the primary amine of vancosamine is not expected to interfere with the complex hydrogen bond network. Based on our previous work on polyproline peptide dynamics in gas phase [1], BODIPY-R6G was coupled to vancosamine without a flexible linker to more closely reflect the conformational changes of the noncovalent complexes.…”
Section: Vancomycin-peptide Noncovalent Complexesmentioning
confidence: 99%
“…It is noteworthy that the detection wavelength was set to 300 nm for avoiding high UV background at low wavelengths, when norvancomycin was present in the mobile phase. Previous studies showed that vancomycin and teicoplanin can form stable non-covalent dimmers or micelle in aqueous solutions [22,23], and this aggregation has been reported to influence positively or negatively the enantioseparation [24][25][26]. Improved chiral selectivity for flurbiprofen and FMOC-amino acid enantiomers was observed by Sun and Olesik when vancomycin was added to the mobile phase on a vancomycin-bonded chiral column (Chirobiotic-V) [27].…”
Section: Chiral Separation By Simultaneous Use Of Norvancomycin As Chmentioning
confidence: 98%